Automatic cleaning system for ceiling fan blade / Muhammad Hafiz Hakimi Zaidi - Zaidi, Muhammad Hafiz Hakimi (2024)
Ceiling fans are a popular choice for comfort in everyday living areas, but their blades frequently attract dust and debris, resulting in inefficiency and the trouble of manual cleaning. This activity takes up time and spreads dust around the area. It is an issue for anyone who wants to keep their living areas clean and their fans working properly. There is an obvious need for a practical solution that streamlines the fan maintenance process, addresses these concerns in a simple-to-use way, and seamlessly fits into users' daily routines. As a result, the solution provides an innovative automatic cleaning system that uses a clever combination that includes an ultrasonic sensor, DC motor, Arduino Uno, LED lights, and a buzzer. Consider a system in which the ultrasonic sensor detects the level of dust and any obstacles on the fan blades, allowing the DC motor to start the cleaning operation. The Arduino Uno controls the movement of spinning brushes or other cleaning mechanisms. The LED lights give visual feedback on the cleaning process, while the buzzer signals the end of the cleaning cycle. This technology not only simplifies fan maintenance but also improves the user experience with real-time feedback and a hassle-free automatic cleaning process. It is a practical, modern approach that promises to transform how to maintain ceiling fans. The primary objectives of this project are to build a system that successfully removes dust and debris from ceiling fan blades, assuring optimal performance and energy efficiency, and to ensure practical deployment by considering factors such as durability, costs, and component accessibility. To summarise, the invention of an autonomous ceiling fan cleaning system offers a viable solution to the ongoing problem of maintaining fan blades. The project is more than just automating a work; it is about improving places and making them aesthetically pleasing locations by taking an efficient and practical approach to fan maintenance.